PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR DI UPTD SMP NEGERI 10 BARRU - Nihrad, Ade; Thahir, Ilyas; Surani; Nurlaelah; Mustamin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Discovery Learning learning model on student learning outcomes in the subject of Islamic Religious Education for grade VIII at UPTD SMP Negeri 10 Barru. This study uses a quantitative approach with an associative research type. The population in this study were all grade VIII students of UPTD SMP Negeri 10 Barru, totaling 148 students, while the research sample was 60 students determined using a simple random sampling technique based on the Slovin formula. Data collection techniques used were observation, interviews, questionnaires, and documentation. The data obtained were analyzed using descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, and hypothesis testing through t-tests, F-tests, and coefficients of determination (R²). The results showed that the pure discovery aspect had a positive and significant effect on student learning outcomes with a t-value of 3.225 > t-table 2.003 and a significance value of 0.002 < 0.05. The guided discovery aspect also has a positive and significant effect with a calculated t value of 2.480 > t table 2.003 and a significance value of 0.016 < 0.05. Furthermore, the laboratory discovery aspect has a positive and significant effect with a calculated t value of 4.593 > t table 2.003 and a significance value of < 0.001 < 0.05. Simultaneously, these three aspects have a significant effect on learning outcomes with a calculated F value of 29.426 > F table 2.769 and a significance value of < 0.001. The coefficient of determination (R²) value of 0.612 indicates that the Discovery Learning model is able to explain 61.2% of the variation in student learning outcomes, while 38.8% is influenced by other factors outside the study. Thus, the Discovery Learning learning model is proven to be effective in improving student learning outcomes in the subject of Islamic Religious Education for class VIII at UPTD SMP Negeri 10 Barru.